Evaluation of an alternative care provider clinic for severe sleep-disordered breathing: a study protocol for a randomised controlled trial. Issue 3 (29th March 2017) - Ip-Buting, Ada; Kelly, Jenny; Santana, Maria J; Penz, Erika D; Flemons, W Ward; Tsai, Willis H; Fraser, Kristin L; Hanly, Patrick J; Pendharkar, Sachin R
Abstract : Introduction: Despite the high prevalence of sleep-disordered breathing (SDB) and the significant health consequences associated with untreated disease, access to diagnosis and treatment remains a challenge. Even patients with severe SDB (severe obstructive sleep apnoea or hypoventilation), who are at particularly high risk of adverse health effects, are subject to long delays. Previous research has demonstrated that, within a sleep clinic, management by alternative care providers (ACPs) is effective for patients with milder forms of SDB. The purpose of this study is to compare an ACP-led clinic (ACP Clinic) for patients with severe SDB to physician-led care, from the perspective of clinical outcomes, health system efficiency and cost. Methods and analysis: The study is a randomised, controlled, non-inferiority study in which patients who are referred with severe SDB are randomised to management by a sleep physician or by an ACP. ACPs will be supervised by sleep physicians for safety. The primary outcome is positive airway pressure (PAP) adherence after 3 months of therapy. Secondary outcomes include: long-term PAP adherence; clinical response to therapy; health-related quality of life; patient satisfaction; healthcare usage; wait times from referral to treatment initiation and cost-effectiveness. The economic analysis will be performed using the perspective of a publicly funded healthcare system. Ethics and dissemination: Ethics approval was obtained from the Conjoint Health Research Ethics Board (ID: REB13-1280) at the University of Calgary. Results from this study will be disseminated through presentations at scientific conferences and publication in peer-reviewed journals. Trial registration number: NCT02191085 ; Pre-results.